2015
DOI: 10.1002/hpm.2317
|View full text |Cite
|
Sign up to set email alerts
|

Developing hospital accreditation standards in Uganda

Abstract: We have demonstrated the feasibility of a self-assessment approach to hospital standards in low-income country setting. This low-cost approach may be used as a good precursor to establishing a national accreditation body, as indicated by the Ministry's efforts to take the next steps. Copyright © 2015 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It is important to note that it is a country with limited resources and no accreditation program. The study used a self-assessment approach with an instrument composed of seven domains and 485 measures (30) .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that it is a country with limited resources and no accreditation program. The study used a self-assessment approach with an instrument composed of seven domains and 485 measures (30) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the authors reported inadequate capacity to sterilise equipment in all hospitals, which would contribute to HCAI. 43 The study reported good provision of running water but no mention of sanitation. Okwaro and colleagues investigated community perception of healthcare improvement intervention in rural Uganda.…”
Section: Resultsmentioning
confidence: 93%
“…While the majority of hospitals reported having infection control protocol in place, only half were recording needle stick injuries and vermin control. 43 Perhaps more surprisingly, 27.5% hospitals were not tracking infection rates even for caesarean sections. In addition, the authors reported inadequate capacity to sterilise equipment in all hospitals, which would contribute to HCAI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This research showed that self-assessment for low-income countries is a low-cost approach and can be used as an excellent precursor to creating a national accreditation institution. [ 14 ]…”
Section: Introductionmentioning
confidence: 99%